Critical behaviour and quantum properties in (Ga,Mn)As - Marshall, Robin Alexander (2013)
pintronics is a rapidly developing field in solid state physics based on the quantum property of spin angular momentum. It has the potential to offer a new generation of electronic devices exploiting spin properties instead of, or in addition to, charge. Such quantum-based devices are expected to demonstrate significant advantages over traditional charge based electronics with a promise of faster data processing speeds and lower power consumption. One of the most widely studied spintronic materials is the dilute magnetic semiconductor gallium manganese arsenide ((Ga,Mn)As). This continues to be a valuable test ground for spintronics applications due to its close relation to the traditional, and well-characterised, semiconductor GaAs, and its relatively high Curie temperature despite values remaining some way off the much sought-after room temperature. The two primary focuses of this thesis are phase-coherent transport and critical phenomena, both of which whilst well understood in metals have seen limited work in (Ga,Mn)As. Critical behaviour in particular has not been extensively studied despite continued disputes over theoretical models and resistance peak positions relative to Curie temperature. Studies of both these areas are presented within this thesis split over four main chapters. The first of these chapters acts as a general introduction to spintronics, and includes both a brief history of the subject, and a theoretical overview focused on the structure and properties of (Ga,Mn)As. This introductory chapter also includes an in-depth review of nanofabrication including typical processing techniques and their applications to the study of spintronics in Nottingham. The second chapter presents a comprehensive study of critical phenomena within (Ga,Mn)As, showing how the behaviour of magnetic properties close to Tc are strongly correlated between samples. Both magnetisation and susceptibility are found to demonstrate behaviour very close to that predicted by the Heisenberg model; a result in strong agreement with theoretical work. The study of critical behaviour is carried over into the third chapter with transport measurements showing that resistance data can be directly used to accurately measure sample Curie temperature by finding the peak in the derivative deltaR/deltaT. This potentially offers an alternate approach to calculating Tc that is faster and cgeaper than the more conventional magnetometry or Arrott plot methods. Analysis is also carried out on the resistance peak which is expected to follow the critical behaviour of the specific heat. The final experimental chapter focuses on the development of nanoring fabrication processes in (Ga,Mn)As including the difficulties associated with fabricating nanoscale structures, the testing performed to achieve high quality, reproducible structures, and the final adopted recipe. This chapter then details early test measurements on these devices including an initial study on the first structures within a dilution refrigerator, and prelimenary work on a second improved batch at 4He temperatures. This work will act as a foundation for the future aim of conducting a full phase-coherence phenomena study in highly optimised (Ga,Mn)As samples grown in Nottingham.